Urban innovation, heterogeneous environmental regulations and haze reduction effects–evidence from pilot policies of innovative cities - Xu, Yue (Frontiers in Environmental Science, 2024)
Innovation-driven development strategies have injected new momentum into haze management. In addition to its core innovation-driven role, innovative city pilot policy is significant for environmental enhancement and should not be overlooked. To assess the performance of the pilot policy in decreasing haze, a multiperiod double difference model was employed, and a spatial econometric model was used to empirically examine the potential spatial spillover effect of haze management as a regional synergistic concept between 2006 and 2020. Panel data from 282 prefecture-level cities were selected. To investigate and empirically examine the territorial spillover effect of haze reduction as a regional synergistic notion, a spatial econometric model was applied. Based on the study, the pilot construction significantly reduced haze pollution. In China's eastern and central regions, small cities, and newer industrial bases, the inhibitory effect of pilot policies on haze pollution was more pronounced, according to heterogeneity analysis. Moreover, analysis of the heterogeneous environmental regulations revealed that the enforcement of policies would increase the sense of urgency of local governments, strengthen the concern and responsibility of the government for the environment, and further awaken the public's concern for the environment, in addition to forcing enterprises to practice clean and sustainable production, thus achieving the effect of accelerated haze reduction. From the spatial perspective, innovative pilot cities have certain spatial spillover effects and thus can increase the effects of policy for neighboring regions, similar economic regions and local transportation regions.